Overview of Nurse Performance in the Inpatient Room of Santa Elisabeth Hospital Medan - Pakpahan, Rotua E.; Saragih, Helinida; Indra Hizkia P; Suryani, Ade Rotua (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2026)
Performance is the result of efforts made by a worker, both in terms of quality and quantity, in accordance with the tasks assigned to him. The successful performance of nurses in managing nursing care depends on the responsibilities they have, knowledge in nursing management, and leadership abilities, in addition to the necessary clinical knowledge and skills, and vice versa, poor nurse performance has an impact on the hospital's image, service quality and patient satisfaction. This study aims to describe the performance of nurses in the inpatient ward of Santa Elisabeth Hospital Medan. This type of research is descriptive quantitative with a cross-sectional approach. The sampling technique uses total sampling with a total sample size of 52 respondents at Santa Elisabeth Hospital Medan. Data collection using nurse performance questionnaire. The data analysis is univariate using a frequency distribution table. The results show that the performance of nurses in the good category amounted to 90.4% and the sufficient category is 9.6%. From the results of this study, it is hoped that the hospital can pay attention to nurses and provide training related to aspects needed to improve service quality.